Biomarker testing experiences among people with lung, colorectal, and breast cancer. Issue 28 (1st October 2022) - Fortune, Erica E.; Saxton, M Claire; Zaleta, Alexandra Katherine
Abstract : 273 Background: Biomarker testing (BT) in oncology is rapidly becoming the standard-of-care across cancer types. There is an established relationship between BT and subsequent prognosis, as well as patient-reported outcomes; thus, the barriers and facilitators for BT are essential to understand. This study investigated the utilization of BT among people diagnosed with cancer and the most frequently experienced BT problems, as well as the person- and systems-level factors associated with BT problems. Methods: We conducted an online survey with adults ( N = 436) diagnosed with either lung (38%), colorectal (35%) or breast cancer (27%) since 2018 (Mean yrs since diagnosis = 2.6, SD = 1.0), across all cancer stages (35% metastatic at diagnosis) and status (31% initial occurrence; 32% recurrence; 28% remission/no current evidence of disease). Participants (68% women; Mean age = 49yrs, SD = 13; 74% Non-Hispanic White) were recruited through a research panel and cancer advocacy organizations. Results: The majority of respondents (85%) reported undergoing BT as part of their cancer care experience. Among those tested, 37% reported experiencing 0 problems with BT, 42% reported 1-2 problems, 15% reported 3-4, and 6% reported 5-7 ( M = 1.4 problems, SD = 1.5). The most commonly cited BT problems were: difficulty understanding results (28%), l ong wait period between test and results (27%), and difficulty scheduling the test (23%). Key sociodemographic (age, gender, income), clinical (cancer diagnosis), and health system variables (insurance type, care setting) were identified as significant bivariate correlates of the number of BT problems experienced. When considering the variables concurrently in a backwards elimination linear regression model (criterion: Probability of F-to-remove > =.10), 5 variables remain in the model explaining 14% of the overall variance, but only 2 variables hold as significant predictors: having Medicaid significantly increased the number of BT problems ( β =.29, p <.001), while receiving care at an academic/comprehensive care center significantly decreased the number of BT problems ( β = -.13, p <.05). Conclusions: The prevalence of BT in our current sample was high, especially compared to rates reported in the existing literature. While this is a promising finding, as is the low overall number of BT problems reported, patients' experience of problems varied; opportunities exist to better support patient understanding of results and testing system delivery (wait time, scheduling). Further, patients with Medicaid and those receiving care outside academic/comprehensive care centers were statistically more likely to report problems, even after controlling for key sociodemographic and clinical variables. As the science of BT continues to evolve and become a cornerstone for cancer care, it is imperative that we continue to address equitable access to BT as well as commonly cited BT problems.